2019
DOI: 10.4103/ajns.ajns_37_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of single burr-hole craniostomy versus twist-drill craniostomy in patients with chronic subdural hematoma

Abstract: Background: Chronic subdural hematoma (CSDH) is predominantly a disease of the elderly. On accounting its risk-to-benefit ratio, there was always controversy regarding the management of the CSDH as to which procedure is superior. Aims: The aim is to compare the clinical and radiological outcomes in patients of CSDH who have undergone single burr-hole craniostomy (BHC) versus twist-drill craniostomy (TDC). Patients and Methods: A retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We found that hematoma density, membrane type, postoperative GOS score, and postoperative drainage time are sig-of CSDH (29), and is the favored surgical option (7). However, some studies recommend TDC over BHC, particularly for older patients with comorbidities (19,22,39).…”
Section: █ Conclusionmentioning
confidence: 84%
“…We found that hematoma density, membrane type, postoperative GOS score, and postoperative drainage time are sig-of CSDH (29), and is the favored surgical option (7). However, some studies recommend TDC over BHC, particularly for older patients with comorbidities (19,22,39).…”
Section: █ Conclusionmentioning
confidence: 84%
“…[32] The risk in the intervention group (and its 95% confidence interval) is based on the assumed risk in the comparison group and the relative effect of the intervention (and its 95% CI) CI confidence interval, OR odds ratio GRADE Working Group grades of evidence High certainty: True effect lies close to that of the estimate of the effect Moderate certainty: The true effect is likely to be close to the estimate of the effect, but there is a possibility that it is substantially different Low certainty: The true effect may be substantially different from the estimate of the effect Very low certainty: The true effect is likely to be substantially different from the estimate of effect The lack of uniform outcomes reporting in patients undergoing surgical evacuation of cSDH is important to consider. [34] For instance, many studies within our meta-analysis defined recurrence as a clinically significant hematoma reaccumulation that warranted re-evacuation [8,10,11,17,27,29], while others measured any reaccumulations as a recurrence. [4,5,21,23,25,26,31,33] Heterogeneity in outcomes reporting was also significant due to highly variable duration of postoperative follow-up ranging from 4 weeks to 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence rates following twist drill trephination are as high as 50% (ranging from 17.4% to 50%). 22,57 Finally, large craniotomy is the most invasive surgical treatment for cSDH. The technique requires general anesthesia and a (>25 mm) bone flap, followed by irrigation and evacuation of the SDH.…”
Section: Imaging Of Csdhmentioning
confidence: 99%